The Form of Presentation of Kejai Nyambei Dance at The Wedding in Kampung Jawa Village, North Lebong District Lebong Regency, Bengkulu Province - Sarah Rahmawani; Susmiarti (Universitas Negeri Padang, 2023)
This study aims to find and describe how the Presentation of Kejai Nyambei Dance at a Wedding Party in Kampung Jawa Village, North Lebong District, Lebong Regency, Bengkulu Province. The type of research is qualitative research using descriptive methods. The instruments used are researchers themselves assisted by supporting instruments such as stationery, cameras, mobile phones, flash drives. The data type uses primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews, and documentation. The steps in analyzing data are data collection, data reduction, data presentation, and conclusions. The results showed that the Kejai Nyambei Dance at the wedding party on May 6, 2023 at 10:30 WIB in Kampung Jawa Village, North Lebong District, Lebong Regency, Bengkulu Province, is a sacred traditional dance with a non-representational form, it is believed that this dance is used as a ritual for the safety of the bride and groom in running the household. The elements of the presentation form of Kejai Nyambei Dance are: (1) Consists of the initial sambei sambah movement, the movement of starting the dance, the movement of being ready to get acquainted, the movement of giving and receiving, the motion of breaking the paddle, the circular motion, the motion of the final sambei sambah, the closing motion, (2) The floor pattern uses a floor pattern of two horizontal straight lines with several different facing directions, (3) This dance music uses three traditional musical instruments, namely kulintang, dap, and gong, (4) Makeup female dancers use beautiful makeup and male dancers do not use any makeup, (5) The costumes used by male dancers use black belango bay clothes, black basic pants, culau, flower brooches, tapis, songket shawls. Female dancers wear red bludru brackets, songket cloth, lotus, net hijab, bun, belt, necklace, bracelet, earrings, flower edit, gold flower, kote-kote, jurai-jurai, round-round, (6) Dancers in pairs with a total of 14 people 7 male dancers and 7 female dancers, (7) The property performed is a long batik cloth, (8) Performed in the arena on the morning when the wedding reception begins with a dance performance duration of 16 minutes 15 seconds.